Meningkatkan Kebahagiaan Remaja Panti Asuhan Dengan Sabar - Zaenal Abidin (UIN Sunan Kalijaga, 2017)
Orphanage teenagers are teenagers who don’t live with family but live together in orphanage home that is assumed to be less affection and less happy then needs to improve their happiness with patient training. The purpose of this study is to see the effectiveness of patient training to improve the happiness of orphanage teenagers in Tlogosari Semarang. The subject of this research are consist of two orphanages located in Tlogosari Semarang, namely PAY Muhammadiyah are consist of 23 children and PAY Nurul Ikhsan are consist of 23 children. The Muhammadiyah group to be an experimental group which for patient training, whereas the Nurul Ikhsan group was not treated but only asked to fill the scale. The happiness scale consist of 8 aspects and 17 items. Patient intervention was given by focus group discussion with 6 cases (corresponding to 6 patient dimensions). The results of this study indicate that the mean experimental group = 50. 3043, whereas the mean control group = 52. 0435. Value t = 1. 409 with df = 22 and significance value .173> 0.05. With the figures of data analysis results, it can be concluded that there is not enough evidence that patient training can improve the orphanage teenager’s happiness in Tlogosari Semarang. Unsuccessful hypothesis of this research is to be expected because religiosity is one of the factor that affect happiness, but it turns out that patient is one of many factor religious teachings. Similarly, the treatment of patient training maybe less intensive so it can’t be the difference between those who are trained and who are not trained. Future research seems to need to replace a patient variable that means hold back replaced with an attribute of gratitude that contains positive emotions. If want to continue using patient as independent variable maybe selected dependent variables such as resilience, adversity intelligence or fortitude.